Martin van Buren and the American Political System - Cole, Donald B. (Book collections on Project MUSE., 1984)
Donald Cole analyzes the political skills that brought Van Buren the nickname Little Magician," describing how he built the Albany Regency (which became a model for political party machines) and how he created the Democratic party of Andrew Jackson. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.